ANALISIS KUALITAS PELAYANAN PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) LARANGAN KECAMATAN HARJAMUKTI KOTA CIREBON - Lourensia Utari Kusumawardani; Ida Hayu Dwimawanti; Susi Sulandari (Journal of Public Policy and Management Review, 2015)
Public services can be defined as any form of fulfillment, either in the form of public goods and public services are in principle the responsibility of and implemented by government agencies in an effort to meet the needs of society as well as in the implementation of the provisions of the legislation. PHC is a Technical Implementation Unit Medical Officer / District (UPTD) which is responsible for the implementation of the health sector in the region. The purpose of this study is to determine and analyze the quality of service Healthy Centre Prohibition Harjamukti District of Cirebon seen from Tangibles dimension, Realibility, Responsiveness, Assurance, and Empathy as well as provide recommendations for improvement of service quality. The method used is descriptive qualitative. The results showed that the quality of PHC services Prohibition of visits of 5 (five) dimensions Zeithaml Tangibles, Realibility, Responsiveness, Assurance, and Empathy is not good, because of the 5 (five) dimensions, there are two (2) dimensions are still poorly namely Tangible and Assurance while the other three dimensions, namely Reliability, Responsiveness and Empathy has been running well. So it can be said not meet the health center services Prohibition of 5 (five) dimension of service by Zeithaml.